Preparo e Otimização de Fotoeletrodos de BiFeO3 para clivagem Fotoeletroquímica da Água - Isaac Péricles Maia de Medeiros (2023)
The conversion of solar energy into chemical energy represents an intriguing strategy for energy transformation and storage. Solar energy conversion can occur through photocatalysis using devices composed of semiconductor photoelectrodes that absorb light with energy equal to or greater than the semiconductor's bandgap, generating charge carriers capable of driving independent reduction and oxidation reactions. In this research, we investigated the influence of temperature on the synthesis of bismuth ferrite nanoparticles (BiFeO3 or BFO) obtained through the sol-gel method and their application as electrodes for photoelectrochemical water splitting. Ethylene glycol was employed as the solvent, combining with precursors (iron and bismuth nitrates in a 1:1 ratio) to form the material referred to as BFO. The powder synthesis involved pre-calcination at 130°C and thermal treatments at various temperatures: 400, 500, 600, 700, 800, and 900°C. Post-processing, materials with a perovskite-type structure were successfully obtained. Thin films were fabricated using the electrophoretic deposition technique to ensure good adhesion of the films to the substrate. With the BFO nanostructures, photocurrent densities of 1.53 µA/cm2 at 1.23 V vs. RHE were achieved for the BFO600 sample under one sun illumination. The ABPE efficiency reached 0.0022% under visible light irradiation. Structural, optical, and morphological properties were studied through X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM/EDS), and photoelectrochemical property determination through voltammetry, Mott-Schottky analysis, and impedance studies. Rietveld analysis revealed a recurring hexagonal perovskite crystal structure across the samples. However, only the samples treated at 500 and 600°C exhibited a monophasic structure (R3c space group) with an average crystal size of approximately 40 nm. In summary, there are promising prospects for applying this composition in the fabrication of photoelectrodes aimed at photoelectrochemical water splitting.